Stability of peanut-based mocha spread containing distilled monoglyceride - Dumadag, Ria Noreen T.
ABSTRACT Three formulation of a peanut-based mocha spread were prepared by mixing mocha flavoring(0.15%), coffee-creamer (6, 8, 10%), sugar (15, 17, 19%) and peanut paste. The effect of different levels (0, 0.5, 1.0, 1.5%) of a stabilizer, Myverol distilled monoglyceride on the formulations was investigated at 37°C (room temperature) for 60 days by measuring the extent of oil separation in the product. Longer storage time significantly α= 0.05 resulted to greater oil separation for all formulations with 0.0 and 0.05% stabilizer. The formulation containing 1.0 and 1.5% stabilizer did not exhibit any oil separation throughout the observation period. The use of 1.0% or greater Myverol distilled monoglyceride is needed for a stable peanut-based mocha spread.